2011
DOI: 10.1016/j.jneumeth.2010.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a head-mounted, eye-tracking system for dogs

Abstract: Growing interest in canine cognition and visual perception has promoted research into the allocation of visual attention during free-viewing tasks in the dog. The techniques currently available to study this (i.e. preferential looking) have, however, lacked spatial accuracy, permitting only gross judgements of the location of the dog's point of gaze and are limited to a laboratory setting. Here we describe a mobile, headmounted, video-based, eye-tracking system and a procedure for achieving standardised calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 34 publications
2
53
0
2
Order By: Relevance
“…In this work, in which the dogs were trained to use a headrest to overcome the eyetracking problem of staying still for light reflections and/or focus, it was found that dogs attended to dogs' faces more than humans' faces. Somppi et al's (2012) experimental arrangement was in contrast to the design by Williams et al (2011), which held the tracking technology on a muzzle on the dog; this system did not constrain the dog's head position but potentially would affect the head movement of the dog.…”
Section: Making Sense Of Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, in which the dogs were trained to use a headrest to overcome the eyetracking problem of staying still for light reflections and/or focus, it was found that dogs attended to dogs' faces more than humans' faces. Somppi et al's (2012) experimental arrangement was in contrast to the design by Williams et al (2011), which held the tracking technology on a muzzle on the dog; this system did not constrain the dog's head position but potentially would affect the head movement of the dog.…”
Section: Making Sense Of Interactionsmentioning
confidence: 99%
“…This work has used head mounted devices with peahens (Kjaersgaard et al, 2008), dogs (Williams et al, 2011), chimpanzees (Kano and Tomonaga, 2013), and rodents (Mueller et al, 2008), and, more recently, off-animal trackers with cameras positioned in front of animals including birds (Schwarz et al, 2013), primates (Tobii Eye Trackers, 2014), cats (Körding et al, 2001) and other vertebrates with laterally placed eyes (Tyrrell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The lemurs followed the gaze of their conspecifics in this real-life environment and showed differential eye-movement patterns when walking compared with being stationary. This head-mounted eye-tracking method has also been used with human infants [21] and with dogs [22] but not with phylogenetically closer animals (i.e., great apes).…”
Section: Introductionmentioning
confidence: 99%
“…Miklósi et al (2004) afirmam que os cães são excelentes modelos para o estudo da evolução social humana porque suas habilidades de compreensão social são um exemplo de evolução convergente: os cães servem como um análogo funcional dos seres humanos. Além disso, são particularmente interessantes no estudo da cognição social, uma vez que são espécies sociais e demonstram sensibilidade a pistas comunicativas (Williams et al, 2011).…”
Section: O Cão Como Sujeito De Estudounclassified
“…De acordo com Williams et al (2011), as regiões preferidas de uma cena são geralmente inspecionadas primeiro e atraem um tempo de observação maior. Padrões de olhar provêm um índice comportamental de processamento perceptual e cognitivo e podem ser índices sensíveis de atenção, motivação e preferência, especialmente quando explorando cenas de alto valor ecológico (Henderson, 2003).…”
Section: Os Cães As Emoções E As Expressões Faciaisunclassified